Rancang Bangun Aplikasi Pendukung untuk Observasi Kelas berbasis Mobile - Feri Setyo Efendi; Lutfi Fanani; Ahmad Afif Supianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In the current era, information and communication technology is almost applied in all types of fields, one of which is education. Mobile applications are one of the breakthroughs in the application of information and communication technology in the field of education. However, there is still no mobile application that helps teachers to make classroom observations. Class observation is really needed by a teacher to help collect data on learning activities in class, where the data will be analyzed to develop teacher quality. At present, the observations made are still manual, which uses a piece of note paper. So that not much data is obtained from observations. As for some observers who started doing classroom observations using a video recorder, which has been better implemented. However, this triggers another problem where an accuracy is needed to match the observer's notes with the video results. The author is encouraged to develop a classroom observation application which produces a timeline of notes, photos, audio, and video. This application was designed using Android Studio with the Waterfall software development method, where the need was clear at the start. Where in consisting of needs analysis, design, implementation and testing. Applications that have been functionally developed will be tested with black-box testing and non-functional will be tested with compatibility testing. In black-box testing applications get 100% valid and the results of compatibility testing applications can be compatible on various android devices with a version above 5.0 (Lolipop).